Theaternarratologie. Ein erzähltheoretisches Analyseverfahren für Theaterinszenierungen - Horstmann, Jan (Narratologia, 2018)
How does theater narrate? Theater narratology thinks narrativity and performativity together. On the basis of narratology and theater studies it develops for the first time an heuristic, analytic model of performative narration that can be practically employed for narratological performance analysis, where the narrative dimension has been hitherto underrepresented.